PL/SQL fundamentals I - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2013)
"The primary objective of this Oracle 11g training course is to provide an introduction to the PL/SQL database programming language covering syntax, structure and features of the language within the context of database applications and programming."--Resource description page.
Title from title screen (viewed August 12, 2013).
Publication date taken from resource description page (Safari, viewed August 12, 2013).
Presenter, Timothy J. Miles.
Keywords: PL/SQL (Computer program language); Oracle (Computer file); Relational databases; Electronic books